2015
DOI: 10.1186/s12878-014-0019-8
|View full text |Cite
|
Sign up to set email alerts
|

The IL-10 polarized cytokine pattern in innate and adaptive immunity cells contribute to the development of FVIII inhibitors

Abstract: BackgroundHemophilia A (HA) is an X-linked inherited bleeding disorder, resulting from a qualitative or quantitative deficiency of clotting factor VIII (FVIII). Antibodies against FVIII, also called inhibitors, block the procoagulant activity of FVIII; thus, impairing hemostatic activity in patients with HA. The exact mechanism underlying the immunological events behind the development of inhibitors remains unknown. This study aimed to understand immune response to FVIII in patients with HA who were either pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
(44 reference statements)
4
12
1
Order By: Relevance
“…This observation suggests that children are admitted to school while already anaemic. This observation is supported by findings of other studies which shows that the prevalence of anaemia is higher among children under the age of five, with prevalence of up to 85% having been reported [43,52]. This observation highlights the need to target anaemia control interventions to younger children within and outside the school system with more emphasis on pre-school age children.…”
Section: Discussionsupporting
confidence: 84%
“…This observation suggests that children are admitted to school while already anaemic. This observation is supported by findings of other studies which shows that the prevalence of anaemia is higher among children under the age of five, with prevalence of up to 85% having been reported [43,52]. This observation highlights the need to target anaemia control interventions to younger children within and outside the school system with more emphasis on pre-school age children.…”
Section: Discussionsupporting
confidence: 84%
“…During early inflammatory response, cytokines such as IL4 and IL10 can be released as an attempt to balance the microenvironment and control inflammation, producing a mixed cytokine profile (Hu et al , ). In this study, the higher levels of IL2 and IL17A found in PUPs when compared with controls also suggest the occurrence of a pro‐inflammatory response mediated by T cells (Oliveira et al , ; Silveira et al , ). Our hypothesis is that IL6 and CXCL8 are secreted in response to an initial inflammatory process occurring in PUPs with HA.…”
Section: Discussionsupporting
confidence: 60%
“…19 The current findings were similar to a previous study in Mwanza, which showed a 77.2% prevalence rate of anemia. 16 The observed high prevalence could be due to deficiency in iron nutritives among under-five children associated with poor food availability, cultural behaviors (which are not necessarily evidence informed and may contribute to nutritional deficits), and maternal factors such as employment. 16 Mothers used thin gruel prepared from cereal (maize, rice, millet, or sorghum) as a major complementary food for their children.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Mwanza, Tanzania reported a prevalence rate of anemia at 77.2% (with mild, moderate, and severe anemia being reported in 16.5%, 33%, and 27.7%, respectively). 16 …”
Section: Introductionmentioning
confidence: 99%